Operations With Excise Goods, Sanctions vs. Misdemeanors - Boiţă, Marius; Dumiter, Florin Cornel; Ajtay, Eduard; Milutin, Ionela Mihaela (Journal of Legal Studies, 2022)
The present work analyzes the trade with excise goods and is addressed to traders of excise goods, entrepreneurs, as well as practitioners in the financial and accounting field, who, in the transactions made with excise goods, may violate the relevant legislation, and may be sanctioned as a contravention, or as the case may be, criminal. Given that the sale of excisable products represents a high fiscal risk, the fiscal authorities have introduced a series of laws, acts, and provisions, including the regulation to use electronic invoicing using the SAF-T (Standard Audit File for Taxation) reporting system, E-invoice or Statement 406 in all situations of trading (excisable) products with high fiscal risk starting from July 2022, by issuing electronic invoices, which bring changes regarding the authorization, movement of excisable products and the procedure for carrying out activities with excisable products, to reduce tax evasion, monitoring, compliance and sanctioning of those who do not comply with excise legislation. In the content of the work, through a case study, we will describe a case regarding non-compliance with the legislation by an entity, how it was sanctioned, and the applicable legislation for this act. The present article considers the current implacable reality, which is, that with the appearance of new rules or obstacles in combating fraud, the methods of fraud have also diversified.